Pengaruh Kompensasi Dan Rekruitmen Terhadap Kinerja Karyawan Pada PT. Indopelita Aircraft Services Tangerang Selatan - Tegar Ferdianzah; Abdul Azis (Yayasan Sahabat Cendekia Jaya, 2024)
This study aims to examine the effect of compensation and recruitment on employee performance at PT Indopelita Aircraft Services Tangerang Selatan, either partially or simultaneously. The research method used in this study is a quantitative method. The samples obtained were 100 respondents using saturated samples. The analytical method used in this study is descriptive statistical analysis, classic assumption test, simple regression, multiple linear regression, analysis of the coefficient of determination (R2), analysis of the correlation coefficient, t test, and f test. The results showed that there was no significant effect of the Compensation Variable (X1) on Employee Performance (Y) at PT Indopelita Aircraft Services, with a tcount of -0.382 < ttable of 1.985 and a significant level of probability sig 0.704 > 0.05. There is a positive and significant effect of the Recruitment Variable (X2) on Employee Performance (Y) at PT Indopelita Aircraft Services, with a tcount of 3.057 > 1.985 and a significance level of 0.003 <0.05. There is a positive and significant effect simultaneously between compensation (X1) and recruitment (X2) on work performance (Y) at PT Indopelita Aircraft Services with an fcount value of 4.799 > 3.089 and a probability significance level of 0.010 <0.05. Multiple linear regression equation Y = 22.305 – 0.036X1 + 0.367X2. The coefficient of determination shows that Compensation (X1), Recruitment (X2) contributes to Employee Performance (Y) of 9%.